PENGARUH TATA KELOLA PERUSAHAAN, CSR, DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Winnie; Mulyana, Ricky Aprilianto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this research was to determine the effect of independence commissioners, managerial ownership, institutional ownership, audit quality, corporate social responsibility, firm size, and environmental uncertainty on earning management. The population of this research consists of non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2019-2021. The number of research samples is 153 companies. The sample selection technique in this research is purposive sampling and uses secondary data obtained from the official website of the Indonesia Stock Exchange. The data are tested and analyzed using multiple regression methods. The results of this study indicate that there is no influence between independence commissioners, managerial ownership, audit quality, corporate social responsibility, firm size, and environmental uncertainty on earnings management, while institutional ownership variables have an influence on earnings management.